Elektroniese pos as rekenaarbemiddelde kommunikasie - Annelie Naudé; H.J. Groenewald (Communicare)
Electronic mail refers to the transfer of one·way electronic messages from one person via an immediate electronic communication system to one or more identified receivers on many cases via computer linked networks such as Internet.] It has become one of the most powerful and useful ways of sending and processing information in the era of the Information Super Highway. Electronic mail is not interpersonal communication because of  it 's a Sinchronic nature but there area number of similarities between  these modes of communication. Users of electronic mail does not regard themselves as part of a faceless mass of people being bombarded with numerous messages because they exercise some control over messages received. Control is a ethical issue in the light of the current availability of pornographic material via Internet. Computer mediated communication seems to open new possibilities in the fields of education and development and these opportunities to reach disadvantaged people. Research require the attention of social and natural scientists alike to ensure that the country will not be reduced to the status of a hitch hiker on the Information Super Highway. This article examines the state of the art in electronic mail research from a communication science perspective and theoretical explanations that could be used to study this "new medium".